Composition

By combining amide slip agent with polysiloxane, the problem of excessive slip agent oxidation and permanent slip agent use in the prior art is solved, and the low coefficient of friction and stable performance of high-density polyethylene resin products are achieved.

CN119604571APending Publication Date: 2025-03-11BOREALIS AG
View PDF 27 Cites 0 Cited by

Patent Information

Application Number
CN202380053657.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-14
Filing Date
2023-07-13
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When existing high-density polyethylene resins are used to make covers and closures, commonly used slip agents are prone to oxidation, resulting in taste and odor problems in food or beverages. At the same time, permanent slip agents such as polydimethylsiloxane are effective but require extensive use, which affects other characteristics.

Method used

Amide slip agents are used in combination with polysiloxane, especially with high density polyethylene, for better performance balance and achieve extremely low coefficient of friction without time-dependent factors.

Benefits of technology

The composition can obtain extremely low coefficient of friction without the use of polysiloxane, and does not depend on time. Compared with the use of amide slip agent alone, the coefficient of friction is even lower, and is suitable for direct use in the formation of injection molded products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240795420000081
    Figure BDA0005240795420000081
  • Figure BDA0005240795420000161
    Figure BDA0005240795420000161
  • Figure BDA0005240795420000162
    Figure BDA0005240795420000162
Patent Text Reader

Abstract

The present invention provides a polymer composition comprising: a) from 99.5 to 95.0 wt%, relative to the total weight of the polymer composition, of a high density polyethylene (HDPE) having a density of from 940 to 980 kg / m3 as determined according to ISO 1183 and an MFR2 of from 0.1 to 5.0 g / 10 minutes as determined according to ISO 1133 under conditions of 190 DEG C and a load of 2.16 kg; b) 0.05 to 0.5 wt%, relative to the total weight of the polymer composition, of at least one amide slip agent; c) 0.1 to 3.0 wt%, relative to the total weight of the polymer composition, of a polysiloxane.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a polymer composition comprising high-density polyethylene (HDPE), an amide slip agent and polysiloxane, which is suitable for making molded articles. The present invention also relates to articles comprising the polymer composition, and the use of the composition for making articles. Background Art

[0002] High-density polyethylene (HDPE) is widely used in molding applications due to its excellent combination of processability and mechanical properties. It is well known that the properties of polyethylene are related to density. The higher the density, the better the stiffness, but the impact properties tend to decrease.

[0003] The present invention relates to a composition comprising a high-density polyethylene resin, which is suitable for preparing injection molded articles, especially caps and closures. In particular, the caps and closures of the present invention can be used to close bottles, such as bottles for carbonated beverages and still beverages.

[0004] Caps and closures are usually made from high density polyethylene resins because they have good mechanical properties, such as stiffness. However, it should be understood that compositions designed for such applications also need to have other properties that are convenient to use. In some cases, a lower coefficient of friction is required to facilitate unscrewing the cap or closure. Typically, a lower coefficient of friction is achieved by adding a slip agent. However, this brings a well-known key problem to the final product. Some commonly used slip agents, such as erucamide, although having the desired properties, can oxidize, thereby causing unpleasant tastes and odors to the food or beverage in the container. Therefore, there is a need to find alternatives.

[0005] EP 1278797 proposes a solution to use saturated amides as slip agents, because these amides do not have the problem of oxidation. However, the slip effect of these saturated amides is often poor. In addition, the slip effect is usually time-dependent, and it usually takes a long time to reach the desired low friction coefficient.

[0006] Another solution is to use permanent slip agents, which are usually solutions based on polydimethylsiloxane (PDMS), which can achieve an immediate slip effect and do not change over time. However, in order to achieve a sufficiently good slip effect, a large amount of PDMS is usually required, which has some disadvantages, including negatively affecting other properties of the composition.

[0007] US2004 / 0176538 describes compositions for making closures or closure liners, comprising a matrix polymer substantially free of erucamide or unsaturated amides, as well as a silicone lubricant and a slip agent. These compositions are taught for preparing liners to be placed in lids, with the specific purpose of avoiding liners from drawing or scratching when the lid is opened. It is reported that the removal torque is comparable to that of compositions containing erucamide. However, in order to achieve this level, a large amount of slip agent needs to be used, which may cause the slip agent to separate out and contaminate the contents of the container. The document does not address the problem of the slip effect being dependent on the time factor.

[0008] There remains a need to provide new compositions that overcome at least some of the above problems. The inventors have surprisingly found that by combining an amide slip agent with a polysiloxane, particularly with a high density polyethylene, a better balance of properties can be achieved. In particular, the composition does not require the use of large amounts of polysiloxane and can achieve an extremely low coefficient of friction that is independent of time. Surprisingly, the coefficient of friction may even be lower than when the amide slip agent is used alone. In addition, the composition is suitable for direct use in forming injection molded articles, such as caps or closures. Summary of the invention

[0009] From one aspect, the present invention provides a polymer composition comprising:

[0010] a) 99.5 to 95.0 wt% of a high density polyethylene (HDPE) having a density of 940 to 980 kg / m2, measured according to ISO 1183, based on the total weight of the polymer composition. 3 , and at 190℃ and 2.16kg load, its MFR 2 0.1 to 5.0 g / 10 min. as determined according to ISO 1133;

[0011] b) 0.05 to 0.5 wt % of at least one amide slip agent, based on the total weight of the polymer composition;

[0012] c) 0.1 to 3.0 wt% of polysiloxane, based on the total weight of the polymer composition.

[0013] Viewed from another aspect the invention provides an article comprising a polymer composition as hereinbefore defined.

[0014] Viewed from another aspect the invention provides the use of a polymer composition as hereinbefore defined in the manufacture of an article, preferably an injection or compression moulded article, such as a cap or closure.

[0015] Detailed description of the invention

[0016] High-density polyethylene (HDPE)

[0017] The polymer of the present invention is a high density ethylene polymer (HDPE). The high density polyethylene can be a homopolymer or a copolymer, but is preferably an ethylene copolymer. An ethylene copolymer refers to a polymer in which most of the weight is from ethylene monomer units (i.e., ethylene accounts for at least 50% wt% of the total weight of the copolymer). The proportion of comonomers is preferably no more than 10% mole, more preferably no more than 5% mole. However, ideally, the comonomer content in the polymer of the present invention is very low, such as 0.1 to 2.0 mol%, for example 0.1 to 1.0 mol%.

[0018] The other copolymerizable monomers are preferably C3-12 α-olefin comonomers, especially C3-10 α-olefin comonomers, especially monoethylene or polyethylene unsaturated comonomers, especially C3-10 α-olefins, such as propylene, 1-butene, 1-hexene, 1-octene and 4-methyl-pent-1-ene. Particularly preferably, 1-hexene, 1-octene and 1-butene or mixtures thereof, especially 1-hexene and 1-butene, are used. Ideally, there is only one comonomer.

[0019] The polymers of the present invention may be unimodal or multimodal.

[0020] The polymer of the present invention is preferably multimodal, ie comprises at least two components. The polymer is preferably bimodal.

[0021] Typically, a polyethylene composition comprising at least two polyethylene components is referred to as "multimodal", which are produced under different polymerization conditions and therefore have different (weight average) molecular weights and molecular weight distributions. Therefore, in this sense, the high density polyethylene polymer of the present invention is preferably a multimodal polyethylene. The prefix "multi" is related to the number of different polymer components that make up the composition. In terms of comonomer content, the polyethylene may also be multimodal.

[0022] The form of the molecular weight distribution curve of such a multimodal polyethylene, ie the appearance of a curve of polymer weight fraction as a function of its molecular weight, will show two or more maxima, or at least be significantly broadened compared to the curves for the individual components.

[0023] For example, if a polymer is produced in a continuous multi-stage process using reactors connected in series and using different conditions in each reactor, the polymer components produced in the different reactors will each have a different molecular weight distribution and weight average molecular weight. When the molecular weight distribution curve of such a polymer is recorded, the individual curves of these components are superimposed into the molecular weight distribution curve of the entire polymer final product, usually resulting in a curve with two or more different maxima.

[0024] The MFR of the high-density polyethylene of the present invention is 20.1 to 5.0 g / 10 minutes. MFR 2 A preferred range is 0.3 to 3.0 g / 10 min, more preferably 0.4 to 2.5 g / 10 min, for example 0.5 to 2.0 g / 10 min.

[0025] The MFR of the high-density polyethylene of the present invention is 21 Preferably it is 15 to 80 g / 10 min, for example 20 to 75 g / 10 min, most preferably 30 to 65 g / 10 min.

[0026] The MFR of the high-density polyethylene of the present invention is 21 / MFR 2 The flow rate ratio (FRR) of the high density polyethylene of the present invention is preferably at least 25.0, such as at least 35.0, more preferably at least 45.0. 21 / MFR 2 The flow rate ratio (FRR) is preferably not more than 80.0, such as not more than 75.0, more preferably not more than 70.0.

[0027] The density of the polymer is between 940 and 980 kg / m 3 Therefore, the polymer of the present invention is high density polyethylene (HDPE). Preferably, the density of the polymer is 950 to 970 kg / m 3 , more preferably 951 to 965 kg / m 3 , even more preferably 952 to 963 kg / m 3 , for example 953 to 961 kg / m 3 .

[0028] The molecular weight distribution (MWD) of the high density polyethylene of the present invention is preferably 7-30, more preferably 9-25, such as 10-20.

[0029] The high density polyethylene of the present invention usually comprises at least a low molecular weight component (A) and a high molecular weight component (B). In a particularly preferred embodiment, the high density polyethylene is composed of components (A) and (B). The weight ratio of component (A) to component (B) is preferably between 30:70 and 70:30, more preferably 35:65 to 65:35, and most preferably 40:60 to 60:40. In some embodiments, the ratio may be 35 to 55 wt% of component (A) and 45 to 65 wt% of component (B), for example 45 to 52 wt% of component (A) and 48 to 55 wt% of component (B), wherein the wt% value is relative to the gross weight of the multimodal high density polyethylene.

[0030] In a particularly preferred embodiment, the wt % values ​​of components (A) and (B) add up to 100%.

[0031] Component (A) and component (B) can each be an ethylene homopolymer or an ethylene copolymer. An ethylene homopolymer refers to a polymer comprising at least 97 mol% (e.g., at least 98 mol%, particularly at least 99.5 mol%) of ethylene monomer units. The definition of the term "ethylene copolymer" is as described above. Most preferably, component (A) is an ethylene homopolymer and component (B) is an ethylene copolymer.

[0032] The high density polyethylene of the present invention is usually produced by a multistage process, wherein components (A) and (B) are produced in subsequent stages. In this case, the properties of the component produced in the second step (or subsequent step) of the multistage process can be inferred from the polymer produced separately in a single stage by applying the same polymerization conditions as in the production stage of the component in the multistage process (e.g. the same temperature, partial pressure of reactants / diluents, suspension medium, reaction time) and using a catalyst that does not contain the polymer produced previously. In addition, the properties of the component produced in the higher stage of the multistage process can also be calculated, for example based on Polymer Processing Conference (Polymer Processing Society), Extended Abstracts and Final Program, Gothenburg, August 19-21, 1997, 4:13 ( Conference on Polymer Processing (The Polymer Processing Society), Extended Abstracts and Final Program, Gothenburg, August 19to 21, 1997, 4:13).

[0033] Thus, although the products of a multi-stage process cannot be measured directly, the identity of the components produced at the higher stages of such a multi-stage process can be determined by applying one or both of the above methods. The skilled person will be able to select the appropriate method.

[0034] High-density polyethylene produced by a multistage process is also known as an "in-situ" blend. The final product consists of an intimate mixture of polymers from two or more reactors, the different molecular weight distribution curves of these polymers together form a molecular weight distribution curve with a broad maximum or two or more maximum values, that is, the final product is a multimodal polymer mixture.

[0035] MFR of low molecular weight component (A) 2 It is usually 100 to 2000 g / 10 minutes, preferably 125 to 1500 g / 10 minutes, more preferably 150 to 1000 g / 10 minutes, for example 200 to 750 g / 10 minutes.

[0036] The density of component (A) may be 955 to 980 kg / m 3 , preferably 960 to 978 kg / m 3 , for example 965 to 975 kg / m 3 .

[0037] Component (A) may be an ethylene homopolymer or copolymer. Preferably, component (A) is an ethylene homopolymer.

[0038] MFR of high molecular weight component (B) 2 It is usually 0.0001 to 1.0 g / 10 minutes, preferably 0.0005 to 0.5 g / 10 minutes, more preferably 0.0008 to 0.1 g / 10 minutes, for example 0.001 to 0.05 g / 10 minutes.

[0039] The density of component (B) may be 925 to 970 kg / m 3 , preferably 930 to 960 kg / m 3 , for example 935 to 950 kg / m 3 .

[0040] Component (B) can be an ethylene homopolymer or copolymer. Component (B) is preferably a copolymer. Preferred ethylene copolymers use α-olefins (e.g., C3-12 α-olefins) as comonomers. Examples of suitable α-olefins include but-1-ene, hex-1-ene, and oct-1-ene. But-1-ene is a particularly preferred comonomer.

[0041] Preparation of high density polyethylene

[0042] The high density polyethylene can be produced by any suitable polymerization process known in the art. In the embodiment where the high density polyethylene is a multimodal high density polyethylene, the high density polyethylene can be produced by polymerization using the conditions for producing multimodal (such as bimodal) polymer products, ideally using Ziegler-Natta (Ziegler Natta) catalyst system. Typically, two or more stages (i.e. multistage) polymerization techniques are used, and different process conditions (such as different temperatures, pressures, polymerization media, hydrogen partial pressures, etc.) are adopted in different stages or regions. Preferably, the multimodal (such as bimodal) composition is produced by multistage polymerization, for example, using a series of reactors, optionally adding comonomers, preferably only adding in the reactor for producing higher / highest molecular weight components. Multistage process is defined as following polymerization technique, wherein, in a separate reaction stage, every kind or at least two polymer components are produced, usually the reaction conditions in each stage are different, and there is a reaction product (including polymerization catalyst) in the previous stage, so as to produce a polymer comprising two or more components. The polymerization reaction used in each stage may involve conventional ethylene homopolymerization or copolymerization, such as gas phase, slurry phase, liquid phase polymerization, using conventional reactors such as loop reactors, gas phase reactors, batch reactors, etc. (see, for example, WO97 / 44371 and WO96 / 18662).

[0043] Preferably, the high density polyethylene is a bimodal high density polyethylene prepared by a two-stage polymerization process.

[0044] The first polymerization stage produces an ethylene homopolymer or an ethylene copolymer, typically an ethylene homopolymer, which is subsequently fed to the second polymerization stage. The second polymerization stage may further produce an ethylene homopolymer or an ethylene copolymer, preferably an ethylene copolymer.

[0045] The first polymerisation stage is preferably a slurry polymerisation step.

[0046] The slurry polymerization is usually carried out in an inert diluent, usually a hydrocarbon diluent, such as methane, ethane, propane, n-butane, isobutane, pentane, hexane, heptane, octane, etc., or a mixture thereof. Preferably, the diluent is a low boiling hydrocarbon having 1 to 4 carbon atoms or a mixture of such hydrocarbons. A particularly preferred diluent is propane, which may contain small amounts of methane, ethane and / or butane.

[0047] The ethylene content in the fluid phase of the slurry may be 1 to 50 mol%, preferably 2 to 20 mol%, and particularly 2 to 10 mol%. The advantage of a high ethylene concentration is that the productivity of the catalyst is increased, but the disadvantage is that more ethylene needs to be recovered than a low concentration.

[0048] The temperature of the first polymerization stage is generally from 60 to 100° C., preferably from 65 to 95° C., more preferably from 70 to 90° C. Excessively high temperatures should be avoided to prevent partial dissolution of the polymer into the diluent and fouling of the reactor. The pressure is generally from 1 to 150 bar, preferably from 40 to 80 bar.

[0049] Slurry polymerization can be carried out in any known reactor for slurry polymerization. Such reactors include continuous stirred tank reactors and loop reactors. Slurry polymerization is particularly preferably carried out in a loop reactor. In these reactors, a circulating pump is used to circulate the slurry along a closed pipeline at high speed. Loop reactors are well known in the art, for example, examples are given in US-A-4582816, US-A-3405109, US-A-3324093, EP-A-479186 and US-A-5391654. Therefore, it is preferred that the first polymerization stage is carried out as slurry polymerization in a loop reactor.

[0050] The slurry can be removed from the reactor continuously or intermittently. The preferred method for intermittent removal is to use a settling leg to first concentrate the slurry and then remove a batch of concentrated slurry from the reactor. The use of settling legs is disclosed in US-A-3374211, US-A-3242150 and EP-A-1310295. Continuous removal techniques are disclosed in EP-A-891990, EP-A-1415999, EP-A-1591460 and WO-A-2007 / 025640. As disclosed in EP-A-1310295 and EP-A-1591460, continuous removal can be combined with an appropriate concentration method. It is preferred to remove the slurry continuously from the first polymerization stage.

[0051] Hydrogen is usually introduced in the first polymerization stage to control the MFR of the resulting polymer. 2 The amount of hydrogen required to achieve the desired MFR depends on the catalyst used and the polymerization conditions. When carrying out slurry polymerization in a loop reactor, a molar ratio of hydrogen to ethylene of 100 to 1000 mol / kmol (or mol / 1000 mol), preferably 200 to 800 mol / kmol, can achieve the desired polymer properties.

[0052] The average residence time of the first polymerization stage is generally 20 to 120 minutes, preferably 30 to 80 minutes. As is well known in the art, the average residence time τ can be calculated by the following formula 1:

[0053] Formula 1: Residence time

[0054]

[0055] Among them, V Ris the volume of the reaction space (the volume of the reactor in a loop reactor and the volume of the fluidized bed in a fluidized bed reactor), Q o is the volume flow rate of the product stream (comprising polymer product and fluid reaction mixture).

[0056] The production rate can be appropriately controlled by the catalyst feed rate. The production rate can also be influenced by appropriate selection of monomer concentration. The desired monomer concentration can be obtained by appropriately adjusting the ethylene feed rate.

[0057] In the second polymerization stage, ethylene is optionally polymerized with at least one alpha-olefin copolymer in the presence of a catalyst and the ethylene polymer produced in the first polymerization stage. It will therefore be appreciated that the second polymerization stage produces an ethylene polymer which is combined with the ethylene polymer produced in the first stage to form the multimodal high density polyethylene of the present invention. Preferred comonomers have been discussed above, but it should be noted that it is particularly preferred if the at least one alpha-olefin is 1-butene.

[0058] The second polymerisation stage is preferably a gas phase polymerisation step, ie carried out in a gas phase reactor. Any suitable gas phase reactor known in the art may be used, such as a fluidised bed gas phase reactor.

[0059] For gas phase reactors, the reaction temperature used is generally between 60 and 115°C (e.g., 70 to 110°C), the reactor pressure is generally between 10 and 25 bar, and the residence time is generally 1 to 8 hours. The gas used is generally a non-reactive gas such as nitrogen, or a low boiling point hydrocarbon such as propane, and a monomer such as ethylene.

[0060] A chain transfer agent (such as hydrogen) is usually added in the second polymerization stage, and the amount of hydrogen added is preferably 50 to 500 mol per 1,000 mol of ethylene.

[0061] The ratio between the first polymerization stage and the second polymerization stage (ie, slurry polymerization and gas phase polymerization) is generally from 30:70 to 70:30, more preferably from 35:65 to 65:35, most preferably from 40:60 to 60:40.

[0062] Prepolymerization

[0063] Prior to the polymerization step discussed above, a prepolymerization step may be performed. The purpose of prepolymerization is to polymerize a small amount of polymer onto the catalyst at low temperature and / or low monomer concentration. By prepolymerization, the performance of the catalyst in the slurry can be improved and / or the properties of the final polymer can be changed. The prepolymerization step is performed in a slurry.

[0064] Thus, the prepolymerization step can be carried out in a loop reactor. Subsequently, the prepolymerization is preferably carried out in an inert diluent, which is generally a hydrocarbon diluent such as methane, ethane, propane, n-butane, isobutane, pentane, hexane, heptane, octane, etc., or a mixture thereof. Preferably, the diluent is a low boiling hydrocarbon having 1 to 4 carbon atoms or a mixture of such hydrocarbons.

[0065] The temperature of the prepolymerization step is generally from 0 to 90°C, preferably from 20 to 80°C, more preferably from 55 to 75°C.

[0066] The pressure is not critical and is generally between 1 and 150 bar, preferably between 40 and 80 bar.

[0067] In the prepolymerization step, the amount of monomer used is generally such that 0.1 to 1000 grams of monomer can be polymerized per gram of solid catalyst component. As known to those skilled in the art, the catalyst particles recovered from the continuous prepolymerization reactor do not all contain the same amount of prepolymer. On the contrary, each particle has its own characteristic amount, which depends on the residence time of the particle in the prepolymerization reactor. Since some particles stay in the reactor for a relatively long time, while some particles stay for a relatively short time, the prepolymer content on different particles is also different, and the prepolymer content on some particles may exceed the above-mentioned limit. However, the average amount of prepolymer on the catalyst is usually within the range specified above.

[0068] The molecular weight of the prepolymer can be controlled by hydrogen, which is well known in the art. In addition, as disclosed in WO-A-96 / 19503 and WO-A-96 / 32420, antistatic additives can be used to prevent the particles from sticking to each other or to the reactor wall.

[0069] When there is a prepolymerization step, it is preferred that the catalyst components are all introduced into the prepolymerization step. However, if the solid catalyst component and the cocatalyst can be fed separately, only part of the cocatalyst can be introduced into the prepolymerization stage, and the remaining part into the subsequent polymerization stage. Moreover, in this case, it is necessary to introduce enough cocatalyst in the prepolymerization stage to obtain a sufficient polymerization reaction.

[0070] It is to be understood that within the scope of the present invention the amount of polymer produced in the prepolymerisation will generally be from 1 to 5 wt% of the final high density polyethylene.

[0071] catalyst

[0072] The polymerization is usually carried out in the presence of a Ziegler-Natta polymerization catalyst. Suitable Ziegler-Natta (ZN) catalysts usually comprise at least one catalyst component, which is formed by a transition metal compound of Group 4 to Group 6 of the Periodic Table of Elements (IUPAC, Nomenclature of Inorganic Chemistry, 1989), a metal compound of Group 1 to Group 3 of the Periodic Table of Elements (IUPAC), an optional compound of Group 13 of the Periodic Table of Elements (IUPAC), and an optional internal organic compound, such as an internal electron donor. The ZN catalyst may also include other catalyst components, such as a co-catalyst and optional external additives.

[0073] Suitable ZN catalysts preferably comprise a magnesium compound, an aluminum compound and a titanium compound supported on a particulate support.

[0074] The particle support may be an inorganic oxide support, such as a support based on silica, alumina, titania, silica-alumina, silica-titania or MgCl 2 Preferably, the carrier is based on silica or MgCl 2 carrier.

[0075] Particularly preferred Ziegler-Natta catalysts are described in EP 1378528 A1 and EP 2994506.

[0076] If a magnesium compound is used, the magnesium compound is preferably the reaction product of a dialkylmagnesium and an alcohol. The alcohol is a linear or branched aliphatic monohydric alcohol. Preferably, the alcohol has 6 to 16 carbon atoms. Branched alcohols are particularly preferred, 2-ethyl-1-hexanol being an example of a preferred alcohol. The dialkylmagnesium can be any compound in which magnesium is bonded to two identical or different alkyl groups. Butyloctylmagnesium is an example of a preferred dialkylmagnesium.

[0077] The aluminum compound is a chlorine-containing alkyl aluminum. Particularly preferred compounds are alkyl aluminum dichloride and alkyl aluminum sesquichloride.

[0078] The transition metal compound of Groups 4 to 6 is preferably a titanium or vanadium compound, more preferably a halogen-containing titanium compound, and most preferably a chlorine-containing titanium compound. A particularly preferred titanium compound is titanium tetrachloride.

[0079] The catalyst can be prepared by contacting the support with the above compounds in sequence, as described in EP 688794 or WO 99 / 51646. Alternatively, the components can be prepared as a solution and then contacting the solution with the support, as described in WO 01 / 55230.

[0080] Another group of suitable ZN catalysts contains a titanium compound and a magnesium halide compound as a support. Thus, the catalyst contains a titanium compound and optionally a Group 13 compound, for example, an aluminum compound on a magnesium dihalide, such as an aluminum compound on magnesium dichloride. For example, such catalysts are disclosed in WO 2005 / 118655, EP 810235, WO 2014 / 096296 and WO 2016 / 097193.

[0081] Suitable activators are Group 13 metal compounds, typically Group 13 alkyl compounds, particularly alkylaluminum compounds, wherein the alkyl group contains 1 to 16 carbon atoms. These compounds include trialkylaluminum compounds, such as trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum and tri-n-octylaluminum; alkylaluminum halides, such as ethylaluminum dichloride, diethylaluminum chloride, ethylaluminum trichloride, dimethylaluminum chloride, etc. Particularly preferred activators are trialkylaluminums, of which triethylaluminum, trimethylaluminum and triisobutylaluminum are particularly useful.

[0082] The amount of activator used depends on the specific catalyst and activator. Typically, triethylaluminum is used in an amount such that the molar ratio of aluminum to transition metal such as Al / Ti is 1 to 1000, preferably 3 to 100, particularly about 5 to 30 mol / mol.

[0083] The optional internal organic compound may be selected from the following classes: ethers, esters, amines, ketones, alcohols, anhydrides or nitriles or mixtures thereof. Preferably, the optional internal organic compound is selected from ethers and esters, most preferably from ethers. Preferred ethers have 2 to 20 carbon atoms, particularly mono-, di- or polycyclic saturated or unsaturated ethers containing 3 to 6 ring atoms. Typical cyclic ethers suitable for the present invention, if used, include tetrahydrofuran (THF), substituted tetrahydrofurans (such as 2-methyltetrahydrofuran), bicyclic ethers (such as 2,2-bis(2-tetrahydrofuranyl)propane, 2,2-bis(2-furanyl)propane) or isomers or mixtures thereof. The internal organic compound is sometimes also referred to as an internal electron donor.

[0084] When producing the high density polyethylene of the present invention, a compounding step is preferably used, wherein the base resin composition, ie the blend obtained from the reactor usually in the form of base resin powder, is extruded in an extruder and then pelletized into polymer particles in a manner known in the art.

[0085] The high-density polyethylene may also contain a small amount of additives, such as pigments, nucleating agents, antistatic agents, fillers, antioxidants, etc., the content of which generally does not exceed 10% by weight, preferably does not exceed 5% by weight.

[0086] Optionally, in the mixing step, additives or other polymer components may be added to the high density polyethylene in the above amounts. Preferably, the high density polyethylene of the present invention obtained from the reactor is mixed with the additives in an extruder in a manner known in the art.

[0087] Composition

[0088] The present invention relates to a composition comprising a high density polyethylene as defined above, at least one amide slip agent and a polysiloxane.

[0089] The polymer composition comprises 95.0 to 99.5 wt% of high-density polyethylene relative to the total weight of the polymer composition. Preferably, the content of high-density polyethylene is preferably 95.5 to 99.0 wt%, more preferably 96.0 to 98.0 wt%, relative to the total weight of the polymer composition.

[0090] The at least one amide slip agent is present in an amount of 0.05 to 0.5 wt % relative to the total weight of the polymer composition. It is preferred if the at least one amide slip agent is present in an amount of 0.08 to 0.4 wt %, more preferably 0.1 to 0.3 wt %, relative to the total weight of the polymer composition.

[0091] The content of polysiloxane is preferably 0.1 to 3.0 wt % relative to the total weight of the polymer composition. It is preferred if the content of polysiloxane is 0.3 to 2.0 wt %, more preferably 0.5 to 1.0 wt %, relative to the total weight of the polymer composition.

[0092] Although polymers other than high-density polyethylene and polysiloxane may be present in the polymer composition within the scope of the present invention, it is preferred if only high-density polyethylene and polysiloxane are contained in the polymer composition.

[0093] The polymer composition is preferably composed of high-density polyethylene, at least one amide slip agent and polysiloxane. For the avoidance of doubt, even if the polymer composition is "composed" of high-density polyethylene, at least one amide slip agent and polysiloxane, conventional polymer additives such as pigments, nucleating agents, antistatic agents, fillers and antioxidants may still be present therein. Therefore, the term "consisting of..." does not mean the exclusion of the presence of polymer additives. However, the term does exclude the presence of other polymer components blended with high-density polyethylene, at least one amide slip agent and polysiloxane. If a carrier polymer is used as part of a masterbatch, the carrier polymer is not excluded. The composition may not contain any other mixed polymers, but may still contain a small amount of carrier polymer for the masterbatch.

[0094] The polymer composition is typically prepared by blending and intimately mixing the components (eg, high density polyethylene, at least one amide slip agent, and polysiloxane), such as by melt mixing in an extruder.

[0095] The polymer composition of the present invention may have a constant or stable coefficient of friction (COF). In particular, the composition may have a coefficient of friction of at most 0.17 or less, preferably 0.16 or less, when measured according to ISO 8295 on injection molded specimens prepared according to ISO 17855-2 within 1 day. Alternatively or additionally, the composition may have a coefficient of friction of at most 0.17 or less, preferably 0.16 or less, when measured according to ISO 8295 on injection molded specimens prepared according to ISO 17855-2 within 14 days. Alternatively or additionally, the composition may have a coefficient of friction of at most 0.17 or less, preferably 0.16 or less, when measured according to ISO 8295 on injection molded specimens prepared according to ISO 17855-2 within 37 days.

[0096] Amide slip agent

[0097] The at least one amide slip agent may be any suitable amide slip agent known in the art. The term "slip agent" is well known to the skilled person, and it is therefore understood that the amide slip agent may be any slip agent comprising at least one amide group. Slip agents are generally used to reduce the force required to remove a closure from a bottle or package.

[0098] In a preferred embodiment, the amide slip agent is a fatty acid amide derivative. The fatty acid amide derivative can be an unsaturated or saturated fatty acid amide derivative, preferably a saturated fatty acid amide derivative.

[0099] Therefore, in one embodiment, the amide slip agent is an unsaturated fatty acid amide, preferably a monounsaturated fatty acid amide, ie, a fatty acid amide derivative containing only one vinyl group.

[0100] Therefore, in one embodiment, the unsaturated fatty acid amide can be one of the following formulas:

[0101] CH 3 (CH 2 ) x CH=CH(CH 2 ) y CONH 2

[0102] Where x and y are independent positive integers.

[0103] In a particularly preferred embodiment, x is a positive integer between 4 and 10, and / or y is a positive integer between 8 and 14, preferably x is 7 and y is 11.

[0104] Therefore, it is particularly preferred that the unsaturated fatty acid amide is:

[0105] CH 3 (CH 2 ) 7 CH=CH(CH 2 ) 11 CONH 2 , that is, erucamide.

[0106] Alternatively, the amide slip agent may be a saturated fatty acid amide. The saturated fatty acid amide may contain 8 to 30 carbon atoms. The saturated fatty acid amide is preferably a straight chain fatty acid amide, expressed as CH 3 (CH 2 )nCONH 2 , wherein n is 6 to 28. Particularly preferred are linear saturated fatty acid amides containing at least 12 carbon atoms and mixtures thereof. Most preferably, the saturated fatty acid amide is selected from the group consisting of behenamide, arachidamide, stearamide, palmitamide, myristicamide and lauramide.

[0107] Within the scope of the present invention, the composition may contain a single amide slip agent or a mixture of two or more different amide slip agents. In this case, if a mixture is present, the mixture may contain only saturated fatty acid amides, or only unsaturated fatty acid amides, or both saturated and unsaturated fatty acid amides. It is most preferred to use a single amide slip agent.

[0108] Polysiloxane

[0109] The polysiloxane may be any suitable polysiloxane. In this context, it is understood that "polysiloxane" refers to a polymer comprising an inorganic siloxane backbone (...-Si-O-Si-O-Si-O-...) wherein two organic groups are attached to each silicon atom.

[0110] It is preferred if the polysiloxane is a high molecular weight polysiloxane or an ultra high molecular weight polysiloxane. It is particularly preferred if the polysiloxane is a poly(dialkyl)siloxane, such as a high molecular weight poly(dialkyl)siloxane or an ultra high molecular weight poly(dialkyl)siloxane.

[0111] In a preferred embodiment, the poly(dialkyl)siloxane is a 1 To C 4Alkyl poly(dialkyl)siloxanes such as polydimethylsiloxane, polydiethylsiloxane, polymethylethylsiloxane, polydipropylsiloxane and polydibutylsiloxane, more preferably polydimethylsiloxane.

[0112] The polysiloxane is preferably a polydisiloxane, such as polydimethylsiloxane, and typically has a kinematic viscosity of at least 5,000,000 cSt, preferably at least 10,000,000 cSt, more preferably at least 15,000,000 cSt. Thus, a typical range is 5,000,000 to 30,000,000 cSt, more preferably 10,000,000 to 25,000,000 cSt.

[0113] The polysiloxane can be used as a pure material or provided as a masterbatch, for example, mixed with a polyolefin (such as polyethylene, polypropylene or a combination thereof). Preferably, the polyolefin is a propylene homopolymer, for example, a propylene homopolymer having a melt flow rate (MFR) of 2 (230°C) of 8 to 18 g / 10 min. Typically, the polysiloxane content in such a masterbatch is at least 25 wt%, more preferably 25% to 60 wt%. Some non-limiting examples of such polysiloxane mixtures include MULTIBASE MB25 series masterbatches, such as MB25-235, all of which are available from Multibase. Alternatively, the polysiloxane can also be provided as a masterbatch mixed with silica, such as available from Wacker. The content of polysiloxane in the Pellet P Plus masterbatch is usually 60 to 95 wt %, such as 70 to 90 wt %, relative to the total weight of the masterbatch.

[0114] It should be understood that the wt% values ​​given above in relation to the amount of polysiloxane in the polymer composition of the invention refer to the amount of polysiloxane itself (and not, for example, the total amount of a masterbatch containing polysiloxane in the composition). Therefore, when the polysiloxane is added as a masterbatch, the percentage content of the polysiloxane in the masterbatch must be taken into account to determine the wt% value of the polysiloxane itself.

[0115] Products

[0116] In addition, the present invention also relates to a product comprising the above composition. The present invention also relates to the use of the composition in manufacturing products.

[0117] In one embodiment, the article comprises at least 90.0 wt% of the composition of the present invention, more preferably at least 95.0 wt%, still more preferably at least 98.0 wt%, such as at least 99.9 wt%, relative to the total weight of the article. It is particularly preferred that the article consists of the composition.

[0118] The article according to the present invention may be an injection molded or compression molded article, preferably an injection molded article, more preferably a cap or closure. These articles may be prepared by conventional methods known in the art.

[0119] It should be understood that any of the above parameters are measured according to the detailed tests given below. For those parameters that have smaller and larger embodiments disclosed, their embodiments are disclosed under the premise of being associated with smaller and larger embodiments of other parameters.

[0120] The invention will now be described with reference to the following non-limiting examples.

[0121] Test method:

[0122] Melt flow rate (MFR)

[0123] Melt flow rate is based on ISO 1133 at 190 ° C and a load of 2.16 kg (MFR 2 ) or 21.6kg(MFR 21 ) conditions.

[0124] Calculate the MFR of components (A) and (B) 2

[0125] logA=x·logB+(1-x)·logC

[0126]

[0127] B = MFR of component (A) 2

[0128] C = MFR of component (B) 2

[0129] A = Final MFR of the multimodal high density polyethylene 2 (mixture)

[0130] X = weight fraction of component (A)

[0131] Flow rate ratio (FRR21 / 2)

[0132] FRR is determined as MFR 21 With MFR 2 ratio.

[0133] Gel Permeation Chromatography (GPC)

[0134] According to ISO 16014-1:2003, ISO 16014-2:2003, ISO 16014-4:2003 and ASTM D 6474-12, the average molecular weight (Mz, Mw and Mn), molecular weight distribution (MWD) and its width are determined by gel permeation chromatography (GPC), which is described by the polydispersity index, that is, PDI = Mw / Mn (where Mn is the number average molecular weight and Mw is the weight average molecular weight). The formula used is as follows:

[0135]

[0136]

[0137]

[0138] For a constant elution volume interval ΔV i , where A i and M i is the chromatographic peak slice area and the molecular weight (MW) of polyolefins, both related to the elution volume V i where N is equal to the number of data points obtained from the chromatogram between the integration limits.

[0139] A high temperature GPC instrument was used, equipped with an infrared detector (IR4 or IR5 from PolymerChar (Valencia, Spain)) equipped with three Agilent-PLgel Olexis and one Agilent-PLgelOlexis Guard columns. The solvent and mobile phase were 1,2,4-trichlorobenzene (TCB), stabilized with 250 mg / L 2,6-di-tert-butyl-4-methylphenol. The chromatographic system was operated at 160°C and a constant flow rate of 1 mL / min. 200 μL of sample solution was injected for each analysis. Data collection was performed using Agilent Cirrus version 3.3 software or PolymerChar GPC-IR control software.

[0140] The column set was calibrated using a universal calibration method (according to ISO 16014-2:2003) using 19 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11500 kg / mol. The PS standards were dissolved at room temperature for several hours. The conversion of polystyrene peak molecular weights to polyolefin molecular weights was performed using the Mark Houwink equation and the following Mark Houwink constants:

[0141] K PS =19x10 -3 mL / g,α PS =0.655

[0142] K PE =39x10 -3 mL / g,α PE =0.725

[0143] K PP =19x10 -3 mL / g,α PP =0.725

[0144] A cubic polynomial fit was used to fit the calibration data.

[0145] All samples were dissolved in the concentration range of 0.5-1 mg / ml at 160°C for 2.5 hours (polypropylene) or 3 hours (polyethylene) with gentle shaking.

[0146] Comonomer content

[0147] Quantitative analysis of microstructure using NMR spectroscopy

[0148] Quantitative nuclear magnetic resonance (NMR) technology was used to quantitatively analyze the comonomer content of the polymer.

[0149] In the molten state, the NMR spectrometer was used to record the spectra at 500.13 and 125.76 MHz. 1 H and 13 Quantification of C 13 C{ 1 H} NMR spectra. All spectra were obtained using 13 A C-optimized 7 mm magic angle spinning (MAS) probe was recorded at 150 °C, with nitrogen used for all pneumatics. Approximately 200 mm of material was loaded into a 7 mm outer diameter zirconium oxide MAS rotor and spun at 4 kHz. This setup was chosen primarily to achieve the high sensitivity required for rapid identification and accurate quantification: {klimke06,parkinson07,castignolles09}. Standard single pulse excitation was used, utilizing the NOE with short recycle delay {pollard04,klimke06} and the RS-HEPT decoupling scheme {fillip05,griffin07}. A total of 1024 (1k) transients were acquired for each spectrum.

[0150] Quantification 13 C{ 1 H} NMR spectra were processed and integrated, and the relevant quantitative properties were determined from the integration. All chemical shifts were internally referenced to the methylene signal (δ+) at 30.00 ppm.

[0151] The ethylene content is quantified by the integration of the methylene (δ+) sites at 30.00 ppm over the number of reported sites for each monomer:

[0152] E=I δ+ / 2

[0153] Correction for the presence of isolated comonomer is made based on the amount of isolated comonomer present:

[0154] E total = E + (3*B + 2*H) / 2

[0155] Where B and H are defined for their respective comonomers. If there is continuous and discontinuous comonomer incorporation, corrections are made in a similar manner.

[0156] Characteristic signals corresponding to 1-butene incorporation were observed, and the comonomer fraction was calculated as the fraction of 1-butene in the polymer relative to all monomers in the polymer:

[0157] fBtotal=(Btotal / (Etotal+Btotal+Htotal)

[0158] The amount of isolated 1-butene incorporated into the EEBEE sequence was quantified by the integration of the *B2 site at 38.3 ppm over the number of reported sites per comonomer:

[0159] B=I *B2

[0160] The amount of 1-butene continuously incorporated into the EEBBEE sequence is quantified by the integration of the ααB2B2 sites at 39.4 ppm over the number of reported sites per comonomer:

[0161] BB=2*IααB2B2

[0162] The amount of discontinuously incorporated 1-butene in the EEBEBEE sequence was quantified by the integration of the ββB2B2 sites at 24.7 ppm over the number of reported sites per comonomer:

[0163] BEB=2*IββB2B2

[0164] Since isolated (EEBEE) and discontinuously incorporated (EEBEBEE) 1-butene overlap at the *B2 and *βB2B2 sites, respectively, the total amount of isolated 1-butene incorporated was corrected based on the discontinuous 1-butene content.

[0165] B=I *B2 -2*I ββB2B2

[0166] The total 1-butene content was calculated from the sum of separated, continuously and discontinuously incorporated 1-butene.

[0167] Total B=B+BB+BEB

[0168] The total mole fraction of 1-butene in the polymer is calculated as:

[0169] fB=(Total B / (Total E+Total B+Total H)

[0170] Characteristic signals corresponding to 1-hexene incorporation were observed, and the comonomer fraction was calculated as the fraction of 1-hexene in the polymer relative to all monomers in the polymer:

[0171] fHtotal=(Htotal / (Etotal+Btotal+Htotal)

[0172] The amount of isolated 1-hexene incorporated into the EEHEE sequence was quantified by the integration of the *B4 site at 39.9 ppm over the number of reported sites per comonomer.

[0173] H=I *B4

[0174] The amount of 1-hexene continuously incorporated in the EEHHEE sequence was quantified by the integration of the ααB4B4 sites at 40.5 ppm over the number of reported sites per comonomer.

[0175] HH=2*IααB4B4

[0176] The amount of discontinuously incorporated 1-hexene in the EEHEHEE sequence was quantified by the integration of the ββB4B4 sites at 24.7 ppm over the number of reported sites per comonomer.

[0177] HEH=2*IββB4B4

[0178] The total mole fraction of 1-hexene in the polymer is calculated as:

[0179] fH=(H total / (E total+B total+H total)

[0180] The mole percentage of comonomer incorporation is calculated from the mole fraction:

[0181] B[mol%]=100*fB

[0182] H[mol%]=100*fH

[0183] The weight percent of comonomer incorporation is calculated from the mole fraction:

[0184] B[wt%]=100*(fB*56.11) / ((fB*56.11)+(fH*84.16)+((1-(fB+fH))*28.05))

[0185] H [wt%] = 100 * (fH * 84.16) / ((fB * 56.11) + (fH * 84.16) + ((1 - (fB + fH)) * 28.05))

[0186] References

[0187] Klimke, K., Parkinson, M., Piel, C., Kaminsky, W., Spiess, H.W., Wilhelm, M., Macromol. Chem. Phys. 2006; 207: 382.

[0188] Parkinson, M., Klimke, K., Spiess, H.W., Wilhelm, M., Macromol. Chem. Phys. 2007; 208: 2128.

[0189] Pollard, M., Klimke, K., Graf, R., Spiess, H.W., Wilhelm, M., Sperber, O., Piel, C., Kaminsky, W., Macromolecules 2004; 37: 813.

[0190] Filip, X., Tripon, C., Filip, C., J. Mag. Resn. 2005, 176, 239

[0191] Griffin, J.M., Tripon, C., Samoson, A., Filip, C., and Brown, S.P., Mag. Res. in Chem. 2007 45, S1, S198

[0192] Castignolles, P., Graf, R., Parkinson, M., Wilhelm, M., Gaborieau, M., Polymer 50(2009)2373

[0193] Busico, V., Cipullo, R., Prog. Polym. Sci. 26(2001)443

[0194] Busico, V., Cipullo, R., Monaco, G., Vacatello, M., Segre, A.L., Macromoleucles 30(1997)6251

[0195] Zhou,Z.,Kuemmerle,R.,Qiu,X.,Redwine,D.,Cong,R.,Taha,A.,Baugh,D.Winniford,B.,J.Mag.Reson.187(2007)225

[0196] Busico,V.,Carbonniere,P.,Cipullo,R.,Pellecchia,R.,Severn,J.,Talarico,G.,Macromol.Rapid Commun.2007,28,1128

[0197] Resconi,L.,Cavallo,L.,Fait,A.,Pimontesi,F.,Chem.Rev.2000,100,1253

[0198] density

[0199] The density of the sample preparation was measured according to ISO 1183 and ISO 1872-2.

[0200] Coefficient of Friction (CoF)

[0201] According to ISO 8295, in 150×80×1mm 3 CoF was measured on thick injection molded specimens. Injection molding was performed in accordance with ISO17855-2. CoF testing was performed on a Zwick Z1.0 S machine. The conditions used were as follows:

[0202] Test speed: 100mm / min±10mm / min

[0203] Measuring distance: 56mm

[0204] Load weight: 200g±2g

[0205] Before measurement, the sample is stored at 23°C and 50% relative humidity for a desired period of time, such as 1 day, 3 days, 7 days, etc.

[0206] experiment

[0207] Material:

[0208] Polysiloxane masterbatch: MULTIBASE TM MB25-235 masterbatch is commercially available from Multibase (the masterbatch contains 25% by weight polysiloxane).

[0209] Slip Agent 1: Finawax S, stearamide, available from Fine Organics.

[0210] Slip Agent 2: Finawax B, behenamide, available from Fine Organics.

[0211] High-density polyethylene (HDPE): Bimodal high-density polyethylene, produced in a pilot plant with ZN catalyst (as disclosed in EP2994506), with a prepolymerization-loop-gas phase reactor configuration, with an MFR of 0.8 g / 10 min and a density of 955.5 kg / m 3 .

[0212] Table 1 shows typical polymerization parameters and final polymer properties of high density polyethylene.

[0213] Table 1

[0214]

[0215]

[0216] Composition and test sample formation

[0217] The required amount of high-density polyethylene powder and additives were premixed in an intensive mixer and then mixed on a ZSK 57 twin-screw extruder. The melt temperature was 210° C. and the production rate was 200 kg / h. The following additives were added: 0.05 wt% of Irganox 1010 (BASF), 0.2 wt% of Irganox 168 (BASF) and 0.05 wt% of CEASIT FI, where wt% is relative to the total weight of the composition (the sum of high-density polyethylene powder + additives is 100%).

[0218] Three compositions were prepared by blending, as shown in Table 2. The blending was carried out on a ZSK 18 twin-screw extruder with a melt temperature of 210°C and an output of 7 kg / h. 3 The friction coefficient was measured on the injection molded specimens for a series of time periods and the results are shown in Table 2.

[0219] As can be seen, the examples of the invention show improved (lower) values ​​that remain consistent over time. The combination of slip agent and polysiloxane in Inventive Example 1 keeps the coefficient of friction constant (which has advantages in terms of shortening storage time to improve production efficiency) and has a lower coefficient of friction, which is advantageous. The coefficient of friction value of Comparative Example 1 is lower, but depends on the time factor. The coefficient of friction of Comparative Example 2 is independent of time, but is undesirably too high.

[0220] Table 2: Composition and properties of molded articles

[0221]

[0222]

[0223] *Added as masterbatch.

Claims

1. A polymer composition comprising a) 99.5 to 95.0 wt% of a high density polyethylene (HDPE) with a density of 940 to 980 kg / m3, measured according to ISO 1183, relative to the total weight of the polymer composition; 3 , and its MFR2 is 0.1 to 5.0 g / 10 min at 190° C. and 2.16 kg load according to ISO 1133; b) 0.05 to 0.5 wt% of at least one amide slip agent, relative to the total weight of the polymer composition; c) 0.1 to 3.0 wt% of polysiloxane relative to the total weight of the polymer composition.

2. The polymer composition according to claim 1, wherein The MFR2 of the high-density polyethylene is 0.3 to 3.0 g / 10 min, preferably 0.4 to 2.5 g / 10 min, and more preferably 0.5 to 2.0 g / 10 min.

3. The polymer composition according to claim 1 or 2, wherein The density of the high-density polyethylene is 950 to 970 kg / m 3 , preferably 951 to 965 kg / m 3 , more preferably 952 to 963 kg / m 3 , even more preferably 953 to 961 kg / m 3 .

4. The polymer composition according to any one of claims 1 to 3, wherein The high density polyethylene is a multimodal polyethylene polymer comprising a low molecular weight (LMW) component (A) and a high molecular weight (HMW) component (B).

5. The polymer composition according to claim 4, wherein The high density polyethylene comprises a low molecular weight (LMW) homopolymer component (A) and a high molecular weight (HMW) ethylene copolymer component (B), preferably, wherein the HMW copolymer component (B) comprises at least one C3-12 alpha olefin, preferably but-1-ene, hex-1-ene and oct-1-ene, more preferably but-1-ene.

6. The polymer composition according to claim 4 or 5, wherein The high-density polyethylene includes 48 to 55 wt% of the high molecular weight component (B) and 52 to 45 wt% of the low molecular weight component (A).

7. The polymer composition according to any one of claims 1 to 6, wherein The amide slip agent is a saturated or unsaturated fatty acid amide.

8. The polymer composition according to claim 7, wherein The amide slip agent is a saturated fatty acid amide, preferably selected from the group consisting of behenamide, arachidamide, stearamide, palmitamide, myristicamide and lauramide.

9. The polymer composition according to any one of claims 1 to 8, wherein The polysiloxane is ultra-high molecular weight polysiloxane.

10. The polymer composition according to any one of claims 1 to 9, wherein The polysiloxane is a poly(dialkyl)siloxane having a C1 to C4 alkyl group, preferably a poly(dimethyl)siloxane.

11. The polymer composition according to any one of claims 1 to 10, wherein The composition comprises 0.08 to 0.4 wt % of the amide slip agent, preferably 0.1 to 0.3 wt %, relative to the total weight of the composition.

12. The polymer composition according to any one of claims 1 to 11, wherein Relative to the total weight of the polymer composition, the composition comprises 0.3 to 2.0 wt % of the polysiloxane, preferably 0.5 to 1.0 wt %.

13. An article comprising the polymer composition of any one of claims 1 to 12.

14. The article of claim 13, wherein: The article is an injection molded or compression molded article, preferably an injection molded article, such as a cap or a closure.

15. Use of a polymer composition as claimed in any one of claims 1 to 12 for the manufacture of an article, preferably an injection moulded or compression moulded article, such as a cap or closure.

Citation Information

Patent Citations

  • Apparatus and method for producing ethylene polymer

    EP0479186A2

  • Procatalyst for ethylene polymer production, method for its preparation and use

    EP0688794A1

  • Polymerization catalyst

    EP0810235A2

  • High solids slurry polymerization

    EP0891990A2

  • Polyethylene composition and method for making shaped objects from same

    EP1278797A1